Toxoplasma gondii RAD51 recombinase is required to overcome DNA replication stress and its inactivation leads to bradyzoite differentiation - Saldarriaga Cartagena, Ana María (2025)
Toxoplasma gondii is an obligate intracellular parasite with a high replication rate that can lead to DNA replicative stress, in turn associated with the generation of DNA double-strand breaks (DSBs). Cells have two main pathways to repair DSBs: non-homologous end joining and homologous recombination repair (NHEJ and HRR respectively). RAD51 is the key recombinase in the HRR pathway. In this work, we achieved endogenous tagging of the RAD51 gene using the Auxin Inducible Degron (AID) system, to generate the clonal line RH RAD51HA-AID. Here we demonstrate that RAD51 is expressed in replicative tachyzoites and establishes damage foci. Auxin-induced knock-down (KD) affects the correct replication of tachyzoites which show loss of synchronization. The use of the RAD51 inhibitor B02 also affects parasite growth, with an IC50 of 4.8 µM. B02 produced alterations in tachyzoite replication and arrest in the S phase of the cell cycle. Additionally, B02 induced tachyzoite to bradyzoite differentiation showing small cyst-like structures. In conclusion, the HRR pathway is necessary for maintaining proper tachyzoite replication under normal growth conditions, supporting that replicative stress occurs during the cell cycle. Our findings also suggest that DNA replication stress can induce bradyzoite differentiation.